'England's Darling' : the Victorian cult of Alfred the Great (MANCHESTER UNIV Press, 2017)
During the last two decades, numerous studies have been devoted to the Victorian fascination with King Arthur, however . the figure of King Alfred has received almost no attention. For much of the nineteenth century, Alfred was as important as Arthur in the British popular imagination. A pervasive cult of the king developed which included the erection of at least four public statues, the completion of more than twenty-five paintings, and the publication of over a hundred texts, by authors ranging from Wordsworth to minor women writers. By 1852, J.A. Froude could describe Alfred's life as 'the.